ANALISIS HUKUM KEBIJAKAN BEBAS VISA KUNJUNGAN DI INDONESIA DALAM PERSPEKTIF HUKUM KEIMIGRASIAN: LEGAL ANALYSIS OF VISA-FREE VISIT POLICY IN INDONESIA FROM THE PERSPECTIVE OF IMMIGRATION LAW - Wiliani, Amalia; Yuspin, Wardah (Fakultas Hukum Universitas Trisakti, 2023)
The obligation to obtain a visa-free visit (BVK) must consider the principles and reciprocal benefits of the country that will receive the BVK from Indonesia. The implementation of this visa-free policy has many impacts, especially on security and public order in Indonesia. The method of writing this article focuses on applicable laws and regulations related to BVK, as well as legal approaches and comparative research to Indonesia's visa-free policy with other Southeast Asian countries. The data used in this study are primary laws, government regulations, and ministerial decisions, as well as secondary sources such as academic articles, books, research reports, and other relevant sources. The latest regulation related to BVK, the Regulation of the Minister of Law and Human Rights Number 22 of 2023 concerning Visas and Stay Permits, states that only ten ASEAN countries are subject to Visa-Free Visits. The presence of foreigners in Indonesia using BVK has committed many immigration violations such as misuse of residence permits, so the implementation of BVK must be calculated and wisely in implementing the BV policy in the context of the Immigration Law, emphasizing the importance of considering the principle of reciprocity and the benefits of immigration law principles for foreigners, namely selective policy, which means that only foreigners who provide benefits are allowed to enter Indonesian territory.